Leadership Management of Eco-Pesantren: Integrating Islamic Values and Environmental Health Principles in Decision-Making - Avif Mulia Rahman; Muchamad Rifqi Hamdani; Zuhri; Khoirul Mualimin; M. Misbahul Munir; M. Munir (PT. Lembaga Penerbit Penelitian Nusantara, 2025)
This study explores the model of leadership and decision-making within Eco-Pesantrens (Islamic boarding schools with an ecological focus) in Indonesia. It investigates how Islamic values (e.g., khalifah [stewardship], mizan [balance], amanah [trust]) are integrated with modern environmental health principles (sustainability, conservation, waste management, ecosystem health) in the strategic and daily decisions of pesantren leaders. Using a qualitative case study approach with in-depth interviews, observation, and document analysis at several pioneering Eco-Pesantrens, this research identifies key leadership paradigms, decision-making processes, and implementation strategies. Findings reveal that successful integration creates a holistic leadership model that aligns spiritual, educational, and environmental objectives. Leaders act as transformative agents, internalizing eco-Islamic theology into institutional policies, curricula, and community practices. The study concludes that the Eco-Pesantren leadership model offers a significant framework for sustainable community development rooted in local religious wisdom. It recommends further development of this paradigm for broader application in Islamic educational institutions and communities facing environmental challenges.